2011
DOI: 10.1038/nnano.2011.118
|View full text |Cite
|
Sign up to set email alerts
|

Deconfinement leads to changes in the nanoscale plasticity of silicon

Abstract: Silicon crystals have an important role in the electronics industry, and silicon nanoparticles have applications in areas such as nanoelectromechanical systems, photonics and biotechnology. However, the elastic-plastic transition observed in silicon is not fully understood; in particular, it is not known if the plasticity of silicon is determined by dislocations or by transformations between phases. Here, based on compression experiments and molecular dynamics simulations, we show that the mechanical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(92 citation statements)
references
References 32 publications
6
86
0
Order By: Relevance
“…This phenomenon was confirmed by our earlier in situ nanomechanical experiments [21] performed on Si nanospheres with radii ranging from 19 to 169 nm, produced by the Hypersonic Plasma Particle Deposition technique. The load (P ) indenter displacement (h) curves recorded for the compressed material revealed two systematic patterns (Fig.…”
Section: Resultssupporting
confidence: 80%
“…This phenomenon was confirmed by our earlier in situ nanomechanical experiments [21] performed on Si nanospheres with radii ranging from 19 to 169 nm, produced by the Hypersonic Plasma Particle Deposition technique. The load (P ) indenter displacement (h) curves recorded for the compressed material revealed two systematic patterns (Fig.…”
Section: Resultssupporting
confidence: 80%
“…They found no phase transformation and only dislocationmediated metal-like plastic deformation. The work by Ge et al 12 suggested that confinement is necessary for CAT in c-Si, and this was later confirmed by Chrobak et al 10 The appropriate constrains on c-Si, for one thing, may improve the stress level in it. Theoretical calculation predicted that the critical von Mises stress to induce CAT in Si is~9.7 GPa ((9/2) 1/2 × the maximum octahedral shear stress of 4.6 GPa).…”
Section: Introductionmentioning
confidence: 89%
“…7,8 The CAT has also been recognized to have a role in the incipient plasticity of bulk c-Si at room temperature. 7,9,10 Stressinduced CAT in Si has in fact been widely observed under various mechanical loading conditions, such as indentation, 6,[10][11][12][13][14][15] ball milling, 16,17 scratching 2,7 and bending. 18,19 Clarke et al 6 firstly reported straining-induced amorphous Si (a-Si) through indentation experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across a number of those research studies, ductility in silicon by large has been attributed either to the occurrence of high pressure phase transformation (HPPT) [1], crystal twinning [2] or surface nucleation of dislocations [3,4]. It is understood that the nucleation of dislocations is more prevalent than HPPT in the presence of free surfaces, for examples in, nanoparticles of silicon [5] while no evidence of crystal twinning during contact loading of silicon has been reported in the literature other than the work of Mylvaganam et al [2]. Reports of HPPT of silicon on the other hand have a richer history [6], and in the past, several phases of silicon were identified [7] by post-experimentation analysis, which are summarised in Table I along with the typical stress levels at which these phases persist.…”
Section: Introductionmentioning
confidence: 99%